Improving Formal Methods Visualizations - Palliyil, Avinash (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2025)
Formal methods encompass mathematical techniques for specifying, validating and verifying software and hardware systems. While they are powerful, their use of technical and mathematical notations can be difficult to understand, validate, and debug for both experts and non-experts. Visualizations are an approach to simplifying this process. In this work, we present some early results from an interview study to understand how users of formal methods use visualizations in their workflow, and apply these findings to Penlloy, a domain-specific visualizer for formal methods.